2022
DOI: 10.31949/educatio.v8i1.1819
|View full text |Cite
|
Sign up to set email alerts
|

Model Read, Answer, Discuss, Explain, and Create untuk Meningkatkan Hasil Belajar IPS Siswa Pada Pembelajaran Daring

Abstract: Latar belakang dilaksanakan penelitian ini adalah masih banyak guru yang merasa kesulitan menjabarkan sintaks model pembelajaran yang ada dan masalah kebingungan guru dalam memilih model pembelajaran yang tepat untuk meningkatkan hasil belajar siswa pada pembelajaran secara daring. Penelitian ini bertujuan untuk mendeskripsikan penerapan Model RADEC (Read-Answer-Discuss-Explain-Create) untuk meningkatkan hasil belajar materi IPS siswa kelas IV SDN Kalimulya 1. Penelitian ini merupakan penelitian tindakan kelas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
1
1
0
1
Order By: Relevance
“…In cycle II all students of class V SDN 10 Palak Aneh achieved a complete score with an average grade score of 91,6 which shows an improvement from cycle I meetings 1 and 2. This is supported by previous research, namely research by Chairunnisa et al, (2022) that the learning model of RADEC effectively improves the learning outcomes of SDN students IPS online learning. Furthermore, the results of the research showed that the model of learning RADEC is effective in improved the learning.…”
Section: Student Learning Outcomes Cycle IIsupporting
confidence: 77%
“…In cycle II all students of class V SDN 10 Palak Aneh achieved a complete score with an average grade score of 91,6 which shows an improvement from cycle I meetings 1 and 2. This is supported by previous research, namely research by Chairunnisa et al, (2022) that the learning model of RADEC effectively improves the learning outcomes of SDN students IPS online learning. Furthermore, the results of the research showed that the model of learning RADEC is effective in improved the learning.…”
Section: Student Learning Outcomes Cycle IIsupporting
confidence: 77%
“…Berdasarkan permasalahan yang dihadapi oleh para guru dan siswa tersebut membuat peneliti merasa perlu adanya inovasi dengan cara melakukan perubahan paradigma pembelajaran dengan menggunakan model dan media pembelajaran yang tepat dan relevan dengan konsep yang diajarkan untuk meningkatkan motivasi dan hasil belajar siswa. Salah satu solusi untuk menangani permasalahan tersebut adalah dengan cara menerapkan model pembelajaran Read, Answer, Discuss,Explain Create (RADEC) agar mempermudah siswa dalam memahami konsep yang diajarkan oleh gurunya (Pratama, Sopandi dan Hidayah, 2019;Chairunnisa, Prihantini dan Sukardi, 2022;Pratama et al, 2020).…”
Section: Pendahuluanunclassified
“…This sudden situation requires quick adjustment by teachers and students. Online learning conducted during the pandemic is not effective; this can be seen from the very low learning outcomes of students (Chairunnisa, 2022). Based on the results of observations that have been made in several junior high schools in the district of fifty cities, several problems were found.…”
Section: Introductionmentioning
confidence: 99%